Undergraduates' perception of health risk of body arts: results of an Italian multicentre study. (20th October 2021) - Marotta, D; Gallè, F; Valeriani, F; Liguori, G; Romano Spica, V; Vitali, M; Protano, C
Abstract: Background: In the last decades, body art practices such as tattooing and piercing have known an increasing popularity, mainly in young people. These procedures are associated with infectious and non-infectious health risks. The aim of this multicenter study was to evaluate the knowledge of health risks related to body art procedures among undergraduate students from ten Italian universities. Methods: A cross-sectional study was performed on undergraduate students attending universities in northern, central and southern Italy. An anonymous questionnaire was administered to the participants for collecting their socio-demographic characteristics and for assessing their knowledge about health risks associated with tattoos and piercing. Results: A total of 2985 students (mean age 23.15 ± 3.99, 73.9% females) completed the questionnaire. 775 (25.9%) of them were from northern Italy, 906 (30.3%) from the Centre and 1324 (44.4%) from the South. More than 90% of the sample were aware that tattoo/piercing procedures can cause health problems. However, the mean values of correct answers about the health risks associated to body art practices were low (5.38 ± 2.39 on a total of 11 correct answers for tattooing and 5.93 ± 3.12 on a total of 14 for piercing). Higher knowledge of the health risks related to tattooing was found among those attending university since more than four years (p < 0.001), life science courses (p < 0.001) and residing/living in the university area (p = 0.023). Those attending North/Centre universities (p < 0.001), since more than 4 years (p < 0.001), life science courses (p < 0.001), and those with graduated father (p = 0.013) had better knowledge of the health risks related to piercing. Conclusions: These results show a lack of knowledge about health risks related to body art practices in the sample. Educational interventions on this issue targeted to youth are needed in Italy. Key messages: Undergraduates do not show a good knowledge of health risks related to tattooing and piercing. Educational interventions are needed to raise youth awareness and knowledge of health risks of body art.